Degradable film and flow battery stack assembly method
By using a biaxial stretching process in the liquid flow battery stack, the degradable film prepared by combining the S-shaped winding method for modular assembly, the problems of low assembly efficiency and insufficient film performance of the liquid flow battery stack are solved, and high efficiency is achieved , environmentally friendly stack assembly and degradation effects.
Patent Information
- Application Number
- CN202411735809.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-29
AI Technical Summary
In the prior art, the assembly efficiency of the flow battery stack is low, and the structural order, crystallinity and tensile strength of the existing degradable films are insufficient, which cannot meet the assembly process requirements of the all-vanadium flow battery stack.
Using a film containing degradable resin, degradable filler, lubricant, plasticizer and antioxidant, the orderly structure and crystallinity of the film are improved through biaxial stretching process, and the liquid flow battery is carried out in combination with the S-shaped winding method. Modular assembly of the stack.
It improves the tensile strength and assembly efficiency of the degradable film, meets the assembly process requirements of the all-vanadium liquid flow battery stack, reduces the generation of leakage current, and can be environmentally friendly after the battery is operated.
Smart Images

Figure CN119481196A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of liquid flow batteries, and in particular to a degradable film and a liquid flow battery stack assembly method. Background Art
[0002] A flow battery stack usually includes end plates on the left and right sides and multiple battery cells. The battery cells are mainly composed of pole frames, electrodes, diaphragms, etc. The two end plates are fixed by screws, and multiple battery cells are pressed and fixed by physical pressure. During assembly, the lower end plate is usually hoisted into place first, and then each battery cell is hoisted into place, stacked in sequence, and pressed with a large press, and finally the upper end plate is hoisted into place. The number of battery cells also varies with the power of the battery stack, and usually dozens or hundreds of battery cells are required. During installation, manual assembly is required one by one, which is not only inefficient, but also has high requirements for assembly workers. If modularization and pre-assembly can be formed, the assembly efficiency can be greatly improved.
[0003] There is also an emerging laser welding sealing technology that can weld the upper and lower pole frames of battery cells to form solid welding points or welds, so that the battery cells can be pre-assembled. However, this method is prone to welding point deformation or breakage under conditions of large temperature differences, resulting in problems such as battery cell position offset and internal component misalignment. In addition, this method cannot achieve overall stacking welding sealing of the battery stack and cannot perform modular assembly.
[0004] For example, patent document CN117855541B proposes a degradable film for liquid flow batteries. The invention can be attached to one or both sides of the surface of the diaphragm layer. It can be punched and positioned to meet assembly requirements, and can also greatly reduce the non-reactive area of the diaphragm layer in the pole frame area, thereby increasing the utilization rate of the diaphragm layer from 60%-75% to 85%-95%. It greatly improves the utilization rate of the diaphragm layer and effectively reduces the generation of additional leakage current, which is of great significance for reducing costs and increasing efficiency of battery stacks and systems.
[0005] However, the structural orderliness, crystallinity and tensile strength of the degradable films produced by the preparation processes of these existing technologies still need to be improved; and the assembly process used in the all-vanadium liquid flow battery stack also needs to be optimized.
[0006] Therefore, according to the above-mentioned related technologies, it is urgent to develop a degradable film and a flow battery stack assembly method. Summary of the invention
[0007] In view of this, the purpose of the present invention is to propose a degradable film and a liquid flow battery stack assembly method, thereby providing a degradable film with a highly ordered structure, crystallinity and good tensile properties; and an assembly process for an all-vanadium liquid flow battery stack with high assembly efficiency.
[0008] Based on the above objectives, the present invention provides a degradable film and a flow battery stack assembly method.
[0009] A degradable film comprises the following raw materials in parts by weight: 90-130 parts of a degradable resin, 80-100 parts of a degradable filler, 5-30 parts of a plasticizer, 1-3 parts of a lubricant, and 0.5-1 parts of an antioxidant;
[0010] The method for preparing the degradable film is as follows:
[0011] Step S1: uniformly mixing the degradable filler and the plasticizer to obtain a thermoplastic elastomer mixture;
[0012] Step S2: feeding the thermoplastic elastomer mixture into a twin-screw extruder for mixing, granulating after cooling, and then drying to obtain thermoplastic elastomer particles;
[0013] Step S3: mixing the thermoplastic elastomer particles, the degradable resin, the lubricant, and the antioxidant, kneading and melting them to obtain a mixed material;
[0014] Step S4: feeding the mixed material into a single screw extruder equipped with a cooling roller, and obtaining a polymer sheet after co-extrusion;
[0015] Step S5: cutting and preheating the polymer sheet, and then biaxially stretching the sheet to obtain a degradable film.
[0016] Preferably, the degradable resin is any one of polybutylene succinate, polylactic acid, terephthalate adipate, polybutylene adipate succinate, carbon dioxide-based plastics, or a combination thereof.
[0017] Preferably, the degradable filler is any one of corn starch, wheat starch, cassava starch, potato starch, rice starch, acetate starch, phosphate starch, oxidized cross-linked starch, or a combination thereof.
[0018] Preferably, the plasticizer is any one of glycerol, ethylene glycol, tung oil anhydride, sorbitol and polyvinyl alcohol, or a combination thereof.
[0019] Preferably, the lubricant is any one of erucamide oleamide, glyceryl monostearate, stearic acid, polyethylene wax, or a combination thereof.
[0020] Preferably, the antioxidant is any one of 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, or a combination thereof.
[0021] Preferably, the weight ratio of the degradable filler to the plasticizer in step S1 is 80-100:5-30;
[0022] During the mixing in step S2, the screw aspect ratio is 40-50:1-1.25, the screw diameter is 20-21 mm, the screw speed is 180-185 rpm, and the temperature is 120-160° C.;
[0023] The temperature of the drying process in step S2 is 45-50°C and the drying time is 5-8h;
[0024] The particle size of the thermoplastic elastomer particles in step S2 is 2.4-2.6 mm;
[0025] The mass ratio of the thermoplastic elastomer particles, the degradable resin, the lubricant and the antioxidant in step S3 is 85-130:90-130:1-3:0.5-1;
[0026] The temperature during mixing and melting in step S3 is 115-155° C. and the screw speed is 180-185 rpm;
[0027] The temperature during co-extrusion in step S4 is 100-155°C;
[0028] The size of the cutting in step S5 is 96-96.2×96-96.2 mm 2 ;
[0029] The preheating temperature in step S5 is 98-90° C. and the preheating time is 60-65 seconds;
[0030] The constant annealing temperature during the biaxial stretching in step S5 is 98-100° C., the stretching ratio is 3.9-4.1×3.9-4.1, the stretching rate is 150-200 mm / s, and the annealing time is 60-65 s.
[0031] Preferably, the thickness of the polymer sheet in step S4 is 0.5-0.55 mm.
[0032] Preferably, the thickness of the degradable film in step S5 is 50-500 μm.
[0033] A method for assembling a flow battery stack, wherein the flow battery stack comprises a bipolar plate, a sealing gasket, a pole frame, a sealing gasket, an electrode, a diaphragm and a degradable film;
[0034] The assembly method of the flow battery stack is as follows:
[0035] Step A1: forming a battery cell in the order of bipolar plate, sealing gasket, pole frame, sealing gasket, electrode, diaphragm layer, electrode, sealing gasket, pole frame and sealing gasket;
[0036] Step A2: Using a degradable film, starting from the electrode and diaphragm middle layer of the first battery cell of the stack, wrap it in an S-shaped manner between the electrode-diaphragm layers of multiple battery cells to form an assembly module, and pre-assemble and modularly assemble the assembly module to obtain a liquid flow battery stack.
[0037] Beneficial effects of the present invention:
[0038] The present invention provides a degradable film and a method for assembling a flow battery stack. The raw materials of the degradable film layer of the present invention are degradable resin, degradable filler, lubricant, plasticizer and antioxidant, all of which are hydrocarbons. They can be degraded during the working process of the flow battery, are environmentally friendly and pollution-free, and have no adverse effects on the electrolyte system of the flow battery. The degradable film of the present invention adopts a biaxial stretching process, which can effectively improve the ordered structure and crystallinity of the film, thereby increasing the tensile strength and meeting the assembly process requirements of the all-vanadium flow battery stack. The degradable film can be used in the assembly process of the all-vanadium flow battery stack. The degradable film of the present invention can be applied to the assembly of all-vanadium liquid flow battery stacks, and multiple battery cells can be assembled into assembly modules by winding inside and outside; the winding of the film can physically pressurize and tighten the parts of the battery cells to prevent them from being dislocated and offset; the pre-assembly and modular assembly of the assembly modules can greatly improve the assembly efficiency during the production of the battery stack; and the degradable film of the present invention can be attached to one or both sides of the surface of the diaphragm layer when it is internally wound, which can be punched and positioned to meet the assembly requirements, and can also greatly reduce the non-reactive area of the diaphragm layer in the pole frame area, greatly improving the utilization rate of the diaphragm layer, and can effectively reduce the generation of additional leakage current. After assembly, since the film is degradable, there is no need for additional removal. When the working electrolyte of the battery stack circulates normally, it can be gradually degraded into carbon dioxide and water, and has no adverse effects on the electrolyte system of the flow battery. Therefore, the present invention has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1It is an assembly diagram of the flow battery stack in the present invention, wherein 1 is a bipolar plate of the first battery cell; 2 is a first sealing gasket of the first battery cell; 3 is an upper pole frame of the first battery cell; 4 is a second sealing gasket of the first battery cell; 5 is an upper electrode of the first battery cell; 6 is a degradable film; 7 is a diaphragm layer; 8 is a lower electrode of the first battery cell; 9 is a third sealing gasket of the first battery cell; 10 is a lower pole frame of the first battery cell; 11 is a fourth sealing gasket of the first battery cell; 12 is an upper pole frame of the second battery cell;
[0041] Figure 2 This is a comparison chart of the elongation at break of the degradable films prepared in the embodiment of the present invention and comparative examples 1 to 12;
[0042] Figure 3 This is a comparison chart of the tensile strength of the degradable films prepared in the embodiment of the present invention and comparative examples 1 to 12. DETAILED DESCRIPTION
[0043] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0044] Example 1: A method for preparing a degradable film and a method for assembling a flow battery stack are as follows:
[0045] S1: 100 g corn starch and 30 g glycerol were mixed uniformly to obtain a thermoplastic elastomer mixture;
[0046] S2: The thermoplastic elastomer mixture was fed into a twin-screw extruder, mixed at 120°C with a screw length-diameter ratio of 40:1, a screw diameter of 20 mm, and a screw speed of 180 rpm, and granulated after being cooled to room temperature, and then dried at 50°C for 8 hours to obtain thermoplastic elastomer particles with a particle size of 2.5 mm;
[0047] S3: 130 g of thermoplastic elastomer particles, 130 g of polybutylene succinate, 3 g of erucamide oleamide, and 1 g of 2,6-di-tert-butyl-p-cresol were mixed, and the mixture was kneaded and melted at 115° C. and a screw speed of 180 rpm to obtain a mixed material;
[0048] S4: feeding the compounded material into a single screw extruder equipped with a cooling roller, and obtaining a polymer sheet with a thickness of 0.5 mm after co-extrusion at 100°C;
[0049] S5: Cut the polymer sheet into 96×96mm 2 After the size was adjusted, the film was preheated at 90°C for 60s, and then biaxially stretched at a constant annealing temperature of 100°C, with a stretching ratio of 4×4 and a stretching rate of 200mm / s. After annealing for 60s, a degradable film with a thickness of 50μm was obtained.
[0050] S6: forming a battery cell in the order of bipolar plate, sealing gasket, pole frame, sealing gasket, electrode, diaphragm layer, electrode, sealing gasket, pole frame and sealing gasket;
[0051] S7: Using a degradable film, starting from the electrode and diaphragm middle layer of the first battery cell of the stack, winding between the electrode-diaphragm layers of multiple battery cells in an S-shaped manner to form an assembly module, pre-assembling and modularly assembling the assembly module to obtain a liquid flow battery stack.
[0052] Example 2: A method for preparing a degradable film and a method for assembling a flow battery stack are as follows:
[0053] S1: 90 g of cassava starch and 25 g of tung oil anhydride are mixed evenly to obtain a thermoplastic elastomer mixture;
[0054] S2: The thermoplastic elastomer mixture was fed into a twin-screw extruder, mixed at 140°C with a screw length-diameter ratio of 45:1.1, a screw diameter of 20.5 mm, and a screw speed of 185 rpm, and granulated after being cooled to room temperature, and then dried at 48°C for 6 hours to obtain thermoplastic elastomer particles with a particle size of 2.6 mm;
[0055] S3: 115 g of thermoplastic elastomer particles, 110 g of polybutylene adipate succinate, 2 g of stearic acid, and 0.8 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate are mixed, and the mixture is kneaded and melted at 130° C. and a screw speed of 185 rpm to obtain a mixed material;
[0056] S4: feeding the compounded material into a single screw extruder equipped with a cooling roller, and obtaining a polymer sheet with a thickness of 0.55 mm after co-extrusion at 130°C;
[0057] S5: Cut the polymer sheet into 96.1×96.1mm 2 After the size was adjusted, the film was preheated at 99°C for 65s, and then biaxially stretched at a constant annealing temperature of 99°C, with a stretching ratio of 4.1×4.1 and a stretching rate of 180mm / s. After annealing for 65s, a degradable film with a thickness of 300μm was obtained.
[0058] S6: forming a battery cell in the order of bipolar plate, sealing gasket, pole frame, sealing gasket, electrode, diaphragm layer, electrode, sealing gasket, pole frame and sealing gasket;
[0059] S7: Using a degradable film, starting from the electrode and diaphragm middle layer of the first battery cell of the stack, winding between the electrode-diaphragm layers of multiple battery cells in an S-shaped manner to form an assembly module, pre-assembling and modularly assembling the assembly module to obtain a liquid flow battery stack.
[0060] Example 3: A method for preparing a degradable film and a method for assembling a flow battery stack are as follows:
[0061] S1: 30 g corn starch, 20 g rice starch, 20 g acetate starch, 10 g phosphate starch, 10 g oxidized cross-linked starch, 5 g glycerol, 5 g ethylene glycol, 5 g tung oil anhydride, and 5 g polyvinyl alcohol are uniformly mixed to obtain a thermoplastic elastomer mixture;
[0062] S2: The thermoplastic elastomer mixture was fed into a twin-screw extruder, mixed at 160°C with a screw length-diameter ratio of 50:1.25, a screw diameter of 21 mm, and a screw speed of 185 rpm, and granulated after being cooled to room temperature, and then dried at 45°C for 5 hours to obtain thermoplastic elastomer particles with a particle size of 2.4 mm;
[0063] S3: 110 g of thermoplastic elastomer particles, 30 g of polybutylene succinate, 10 g of terephthalic acid butylene adipate, 30 g of polybutylene adipate succinate, 30 g of carbon dioxide-based plastic, 1 g of polyethylene wax, 0.2 g of 2,6-di-tert-butyl-p-cresol, and 0.4 g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] were mixed, and kneaded and melted at 115° C. and a screw speed of 185 rpm to obtain a mixed material;
[0064] S4: The compounded material was fed into a single screw extruder equipped with a cooling roller, and a polymer sheet with a thickness of 0.5 mm was obtained after co-extrusion at 155°C;
[0065] S5: Cut the polymer sheet into 96.2×96.2mm 2 After the size was adjusted, the film was preheated at 98°C for 60s, and then biaxially stretched at a constant annealing temperature of 98°C, with a stretching ratio of 3.9×3.9 and a stretching rate of 150mm / s. After annealing for 60s, a degradable film with a thickness of 500μm was obtained.
[0066] S6: forming a battery cell in the order of bipolar plate, sealing gasket, pole frame, sealing gasket, electrode, diaphragm layer, electrode, sealing gasket, pole frame and sealing gasket;
[0067] S7: Using a degradable film, starting from the electrode and diaphragm middle layer of the first battery cell of the stack, winding between the electrode-diaphragm layers of multiple battery cells in an S-shaped manner to form an assembly module, pre-assembling and modularly assembling the assembly module to obtain a liquid flow battery stack.
[0068] Comparative Example 1:
[0069] Compared with Example 1, this comparative example does not stretch the polymer sheet during the preparation of the degradable film, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0070] Comparative Example 2:
[0071] Compared with Example 1, this comparative example only replaces "annealing for 60 seconds" with "annealing for 0 seconds", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0072] Comparative Example 3:
[0073] Compared with Example 1, this comparative example only replaces "annealing for 60 seconds" with "annealing for 180 seconds", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0074] Comparative Example 4:
[0075] Compared with Example 1, this comparative example only replaces the "stretching rate of 200 mm / s" with "stretching rate of 25 mm / s", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0076] Comparative Example 5:
[0077] Compared with Example 1, this comparative example only replaces the "stretching rate of 200 mm / s" with "stretching rate of 75 mm / s", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0078] Comparative Example 6:
[0079] Compared with Example 1, this comparative example only replaces the "stretching rate of 200 mm / s" with "stretching rate of 300 mm / s", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0080] Comparative Example 7:
[0081] Compared with Example 1, this comparative example only replaces "biaxial stretching at a stretching rate of 200 mm / s and annealing for 60 seconds" with "biaxial stretching at a stretching rate of 25 mm / s and annealing for 0 seconds", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0082] Comparative Example 8:
[0083] Compared with Example 1, this comparative example only replaces "biaxial stretching at a stretching rate of 200 mm / s and annealing for 60 seconds" with "biaxial stretching at a stretching rate of 25 mm / s and annealing for 180 seconds", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0084] Comparative Example 9:
[0085] Compared with Example 1, this comparative example only replaces "biaxial stretching at a stretching rate of 200 mm / s and annealing for 60 seconds" with "biaxial stretching at a stretching rate of 75 mm / s and annealing for 0 seconds", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0086] Comparative Example 10:
[0087] Compared with Example 1, this comparative example only replaces "biaxial stretching at a stretching rate of 200 mm / s and annealing for 60 seconds" with "biaxial stretching at a stretching rate of 75 mm / s and annealing for 180 seconds", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0088] Comparative Example 11:
[0089] Compared with Example 1, this comparative example only replaces "biaxial stretching at a stretching rate of 200 mm / s and annealing for 60 seconds" with "biaxial stretching at a stretching rate of 300 mm / s and annealing for 0 seconds", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0090] Comparative Example 12:
[0091] Compared with Example 1, this comparative example only replaces "biaxial stretching at a stretching rate of 200 mm / s, annealing for 60 seconds" with "biaxial stretching at a stretching rate of 300 mm / s, annealing for 180 seconds", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a degradable film is obtained;
[0092] Performance testing and data analysis:
[0093] Referring to GB / T1040.3-2006 "Test for tensile properties of plastics", a strip sample with a width of 15 mm, a length of 150 mm and parallel markings with an interval of 50 mm in the middle was prepared by cutting method, and the tensile strength (MPa) of the degradable films prepared in Examples 1 to 3 and Comparative Examples 1 to 12 was tested using a universal material testing machine (Instron@6800, Instron) at a speed of 50 mm / min; the test results are shown in FIG. Figure 2 As shown;
[0094] Referring to GB / T1040.3-2006 "Test for tensile properties of plastics", a strip sample with a width of 15 mm, a length of 150 mm and parallel markings with an interval of 50 mm in the middle was prepared by cutting. The elongation at break (%) of the degradable films prepared in Examples 1 to 3 and Comparative Examples 1 to 12 was tested using a universal material testing machine (Instron 6800, Instron) at a speed of 50 mm / min. The test results are shown in the figure. Figure 3 As shown;
[0095] Combination Figure 2 and Figure 3 It can be seen that after biaxial stretching, the tensile strength of the degradable film prepared in the embodiment of the present invention is increased to 210MPa at most compared with that before stretching; however, due to the directional structure of the polymer chain induced by the biaxial stretching process and the increase in crystallinity, the elongation at break of the film is reduced to 75%-99.5% compared with that before stretching. From the comparison of various data, it is known that the optimal stretching rate is 150-200mm / s, and the optimal annealing time is 60-65s, and all the data are relatively excellent.
[0096] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0097] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A degradable film, characterized in that: The raw materials include the following parts by weight: 90-130 parts of degradable resin, 80-100 parts of degradable filler, 5-30 parts of plasticizer, 1-3 parts of lubricant, and 0.5-1 parts of antioxidant; The method for preparing the degradable film is as follows: Step S1: uniformly mixing the degradable filler and the plasticizer to obtain a thermoplastic elastomer mixture; Step S2: feeding the thermoplastic elastomer mixture into a twin-screw extruder for mixing, granulating after cooling, and then drying to obtain thermoplastic elastomer particles; Step S3: mixing the thermoplastic elastomer particles, the degradable resin, the lubricant, and the antioxidant, kneading and melting them to obtain a mixed material; Step S4: feeding the mixed material into a single screw extruder equipped with a cooling roller, and obtaining a polymer sheet after co-extrusion; Step S5: cutting and preheating the polymer sheet, and then biaxially stretching the sheet to obtain a degradable film.
2. The degradable film according to claim 1, characterized in that: The degradable resin is any one of polybutylene succinate, polylactic acid, terephthalate butylene adipate, polybutylene adipate succinate, carbon dioxide-based plastics, or a combination thereof.
3. The degradable film according to claim 1, characterized in that: The degradable filler is any one of corn starch, wheat starch, cassava starch, potato starch, rice starch, acetate starch, phosphate starch, oxidized cross-linked starch, or a combination thereof.
4. The degradable film according to claim 1, characterized in that: The plasticizer is any one of glycerol, ethylene glycol, tung oil anhydride, sorbitol, polyvinyl alcohol, or a combination thereof.
5. The degradable film according to claim 1, characterized in that: The lubricant is any one of erucamide oleamide, glyceryl monostearate, stearic acid, polyethylene wax, or a combination thereof.
6. The degradable film according to claim 1, characterized in that: The antioxidant is any one of 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, or a combination thereof.
7. The degradable film according to claim 1, characterized in that: The weight ratio of the degradable filler to the plasticizer in step S1 is 80-100:5-30; During the mixing in step S2, the screw aspect ratio is 40-50:1-1.25, the screw diameter is 20-21 mm, the screw speed is 180-185 rpm, and the temperature is 120-160° C.; The temperature of the drying process in step S2 is 45-50°C and the drying time is 5-8h; The particle size of the thermoplastic elastomer particles in step S2 is 2.4-2.6 mm; The mass ratio of the thermoplastic elastomer particles, the degradable resin, the lubricant and the antioxidant in step S3 is 85-130:90-130:1-3:0.5-1; The temperature during mixing and melting in step S3 is 115-155° C. and the screw speed is 180-185 rpm; The temperature during co-extrusion in step S4 is 100-155°C; The size of the cutting in step S5 is 96-96.2×96-96.2 mm 2 ; The preheating temperature in step S5 is 98-90° C. and the preheating time is 60-65 seconds; The constant annealing temperature during the biaxial stretching in step S5 is 98-100° C., the stretching ratio is 3.9-4.1×3.9-4.1, the stretching rate is 150-200 mm / s, and the annealing time is 60-65 s.
8. The degradable film according to claim 1, characterized in that: The thickness of the polymer sheet in step S4 is 0.5-0.55 mm.
9. The degradable film according to claim 1, characterized in that: The thickness of the degradable film in step S5 is 50-500 μm.
10. A method for assembling a flow battery stack according to any one of claims 1 to 9, characterized in that: The flow battery stack comprises bipolar plates, sealing gaskets, pole frames, sealing gaskets, electrodes, diaphragms and degradable films; The assembly method of the flow battery stack is as follows: Step A1: forming a battery cell in the order of bipolar plate, sealing gasket, pole frame, sealing gasket, electrode, diaphragm layer, electrode, sealing gasket, pole frame and sealing gasket; Step A2: Using a degradable film, starting from the electrode and diaphragm middle layer of the first battery cell of the stack, wrap it in an S-shaped manner between the electrode-diaphragm layers of multiple battery cells to form an assembly module, and pre-assemble and modularly assemble the assembly module to obtain a liquid flow battery stack.
Citation Information
Patent Citations
Ion exchange membrane, preparation method thereof and flow battery
CN117855541B
High-strength and high-toughness biodegradable film and preparation method thereof
CN106433047A
Fuel cell stack based on modular design and manufacturing method thereof
CN109950593A
Battery module
CN113178656A
Fuel cell stack structure and assembling method thereof
CN114497669A
